(untitled) (Bioresearch Communications, 2024)
Background: This study investigates the prevalence and characteristics of E. coli resistance patterns, focusing on isolates from patients with urinary tract infections (UTIs), diarrheal illnesses, and healthy controls. Methods: The study collected and identified E. coli isolates from 36 individuals: 17 with UTIs (urine samples), 6 with diarrhea (stool samples), and 13 healthy controls (stool samples). Antimicrobial susceptibility testing (AST) was performed to assess resistance against ten antibiotics from eight classes. Fluoroquinolone resistance was further evaluated against four drugs (nalidixic acid, ciprofloxacin, ofloxacin, and moxifloxacin). Additionally, molecular analysis of quinolone resistance-determining regions (QRDRs) in gyrA, gyrB, parC, and parE genes was performed on two selected isolates (U44 and U46) by genome sequencing. Results: Chloramphenicol and meropenem displayed the highest efficacy (>70% sensitivity), while AZM, AML, NA and SXT showed the highest resistance. UTI isolates exhibited higher resistance than diarrheal and healthy control counterparts. Worryingly, 58% of isolates exhibited multidrug resistance (MDR), with most (13/21) originating from UTI patients. The presence of MDR E. coli in five healthy individuals suggests potential carriage and community transmission. Fluoroquinolone resistance was particularly alarming, with moxifloxacin showing the highest resistance (80.95%). Molecular analysis confirmed mutations in all three fluoroquinolone resistance determining genes except gyrB. S84L and D87N dual mutations in the QRDR of gyrA was found in both isolates. S80I and S458A single mutations were observed in parC and parE, respectively. Conclusion: The study findings highlight the widespread prevalence of antibiotic resistance in E. coli and the urgent need for alternative treatment strategies. Bioresearch Commu. 10(2): 1532-1538, 2024 (July)